Housing and household wealth inequality: Evidence from the People's Republic of China - Sheng Li; Jie Li; Alice Y. Ouyang (Asian Development Bank Institute (ADBI), 2017)
We examine the issue of the widening wealth inequality in the People's Republic of China (PRC) from the perspective of housing. Using China Household Finance Survey (CHFS) data from 2011, we find that the PRC's wealth inequality including housing is much larger than income inequality. Housing value appreciation, in particular, contributes to wealth inequality by allowing households to enjoy equity market premium through investing more in equity markets and taking a higher position in risky assets.
Keywords: E44; O11; O15; 330; Economics; China; People's Republic of